Caracterização do perfil de microvesículas circulantes em pacientes pediátricos com Leucemia Linfoblástica Aguda de células B submetidos à quimioterapia de remissão - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Microvesicles (MVs) correspond to a heterogeneous group of vesicles derived from plasma membrane, released by normal cells and cancer cells. Their presence in biological fluids can be associated with the severity of pathological processes, having highlighted their role as potential biomarkers of diseases and therapeutic targets. Thus, the present study sought to characterize the profile of circulating MVs in B-cell Acute Lymphoblastic Leukemia (B-ALL) pediatric patients de novo submitted to remission chemotherapy. This is a descriptive, longitudinal retrospective study, carried out at the Fundação Hospitalar de Hematologia e Hemoterapia do Amazonas (HEMOAM) in partnership with the Grupo Integrado de Pesquisa em Biomarcadores (GIPB) of the Instituto Rene Rachou (IRR) - Fiocruz Minas. From samples stored in the biorepository of the Multidisciplinary Laboratory of the Fundação HEMOAM, 10 bone marrow (BM) samples and 10 peripheral blood (PB) samples from B-ALL patients collected at three moments of remission induction therapy were selected , referred to as: day of diagnosis (D0), day 15 (D15) and end of remission induction therapy (D35). In addition, 10 PB samples from children without leukemia were also selected (single time point). Subsequently, the samples were sent to the IRR, with the GIPB, where the was carried out immunophenotypic characterization of MVs derived from neutrophils (NEU-MVs), monocytes (MON-MVs), T lymphocytes (TL-MVs), erythrocytes (E-MVs), platelets (P-MVs), endothelial cells (EC-MVs) and leukemic cells (LC-MVs) using the flow cytometry. Our results demonstrated that B-ALL patients had a significant increase in EC-MVs, along with LC-MVs CD10+ compared to the control group. In addition, the evaluation of the kinetics of circulating MVs during induction therapy demonstrated a significant decline in LC-MVs with phenotype CD10+ and CD19+ at D35. Finally, through integrative networks at D35, it was demonstrated that B-ALL patients exhibit a network rich in interactions between MVs populations, profile opposite to D0. As far as we know, this is the first study that describes the levels and kinetics of circulating MVs derived from inflammatory leukocytes and LCs in B-ALL patients.
Characterization of the circulating microvesicles profile in B-cell Acute Lymphoblastic Leukemia pediatric patients undergoing remission chemotherapy
Keywords: Leucemia em crianças; Leucemia linfoblastica; CIENCIAS BIOLOGICAS: IMUNOLOGIA: IMUNOLOGIA APLICADA; CIENCIAS DA SAUDE: MEDICINA: CLINICA MEDICA: CANCEROLOGIA; Leucemia infantil; Vesículas extracelulares; Microambiente leucêmico; Citometria de fluxo; Biomarcadores